Optimization of Electronic Control for a Monohull Leisure Boat Using Meteorological Data to Enhance Stability and Safety in Coastal Environments - Muhammad Ramdhani Setyo Nugroho; Thalia Salsabila; Yobel Eliezer Mahardika; Rizky Ramadhani; Anton Widodo (Journal of Computation Physics and Earth Science (JoCPES), 2025)
Indonesia’s maritime geography offers significant potential for marine tourism but requires transportation systems capable of operating safely under variable coastal environmental conditions influenced by wind and wave variability. This study presents the design and evaluation of a compact monohull leisure boat integrated with an Electronic Remote Control (ERC) system to improve maneuverability and operational safety. The research applies an engineering design approach involving regression-based estimation of principal dimensions, digital hull modeling using Maxsurf, static stability evaluation through righting arm (GZ) analysis, and spatial optimization using a General Arrangement (GA) plan. Five alternative hull geometries were developed and analyzed to identify the most suitable configuration for marine tourism operations. The stability analysis indicates that all hull models exhibit positive righting arm values within the evaluated heel angle range, confirming adequate static stability under typical coastal conditions. Among the evaluated configurations, Model 4 demonstrates the most favorable stability characteristics. The integration of the ERC system further enhances vessel maneuverability and reliability during low-speed navigation and docking, supporting safer marine tourism transportation in coastal waters.